2017
DOI: 10.1038/ijo.2017.220
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-treatment microbial Prevotella-to-Bacteroides ratio, determines body fat loss success during a 6-month randomized controlled diet intervention

Abstract: On the basis of the abundance of specific bacterial genera, the human gut microbiota can be divided into two relatively stable groups that might have a role in personalized nutrition. We studied these simplified enterotypes as prognostic markers for successful body fat loss on two different diets. A total of 62 participants with increased waist circumference were randomly assigned to receive an ad libitum New Nordic Diet (NND) high in fiber/whole grain or an Average Danish Diet for 26 weeks. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
104
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 19 publications
11
104
2
Order By: Relevance
“…In this study, nonobese ETP individuals showed greater BMI loss than ETB individuals after our 3-week intervention. Similar findings were also reported in overweight individuals that high Prevotella/Bacteroides ratio group had higher weight loss than low Prevotella/Bacteroides ratio group when receiving the New Nordic Diet [17] and a 500 kcal/day energy deficit diet [9]. Importantly, we successfully constructed a BMI loss ratio prediction model based on baseline relative abundance of 7 gut microbial species.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, nonobese ETP individuals showed greater BMI loss than ETB individuals after our 3-week intervention. Similar findings were also reported in overweight individuals that high Prevotella/Bacteroides ratio group had higher weight loss than low Prevotella/Bacteroides ratio group when receiving the New Nordic Diet [17] and a 500 kcal/day energy deficit diet [9]. Importantly, we successfully constructed a BMI loss ratio prediction model based on baseline relative abundance of 7 gut microbial species.…”
Section: Discussionsupporting
confidence: 75%
“…The observed association of TMAO with glycemic status agrees with previously published data. 39,40 These results suggest that the method can in fact detect physiologically relevant differences in TMAO, and that our observed lack of effect of short-term flavanol intervention on measured TMAO reflects a true lack of effect in terms of physiological relevance of TMAO.…”
Section: Health Status and Other Predictorsmentioning
confidence: 70%
“…This strategy has already been applied to identifying microbiome characteristics that predict the efficacy of diet-based weight loss programs. 40 Measurements that might prove useful would be baseline and post-intervention (1) levels (DNA abundance by 16S rDNA sequencing) and activity (metabolic activity by converting 16S rRNA to cDNA and sequencing) of the strains of bacteria identified as releasing TMA from dietary precursors, 4 (2) targeted functional metagenomics and metatranscriptomics of microbial genes in the biosynthetic pathway, 16 (3) ex vivo assessment of the capacity for TMA release in subjects fecal samples, and (4) hepatic FMO3 expression levels. The significant intra-individual variation observed for TMAO concentrations could be due differences in the TMA-releasing capacity of the gut microbiome and hepatic FMO3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…plasma glucose, triglycerides, insulin, cholesterol) rather than weight loss [28]. The one 49 published study that directly investigated the relationship between baseline microbiota structure 50 and long-term weight loss found that a high fecal Prevotella/Bacteroides (P/B) ratio (> 0.01, n = 51 15) at baseline resulted in a mean of 1.31kg more weight loss at 6 months than a low P/B ratio 52 (P/B < 0.01, n = 21) [32]. No studies have investigated the impact of microbiota on adherence to 53 2 a dietary intervention.…”
mentioning
confidence: 99%
“…This could be due to 269 our small sample size (n=25-34 for any diet-cohort combination), indeed, only ∼ 20% of ASV-270 clusters were detected in at least half of the subjects on either diet, limiting our statistical power 271 to identify differences between VS and US subjects. Although our sample size was comparable to 272 other published studies investigating the gut microbiota and diet responsiveness [32,38,18], our 273 analysis included stringent filtering of samples with at least 10,000 reads and ASV-clusters present 274 in at least 10% of subjects on the focal diet. We also included replicate samples for most subjects 275 in order to reduce false positive identification during differential abundance testing.…”
mentioning
confidence: 99%